Defining the quantitative aspects of dominant tolerance induction and maintenance - Caridade, Marta Ribeiro Lopes, 1982- (2013)
Tese de doutoramento, Ciência Biomédicas (Imunologia), Universidade de Lisboa, Faculdade de Medicina, 2013